A Design And Construction Of A Letter Processing System In Silaberanti Village: A Letter Processing System In Silaberanti Village - Rendi Rendi (International Journal Cister, 2022)
Silberanti Village is a sub-district in Jakabaring sub-district, Palembang city. One of the tasks of the village is to collect initial population data, where the implementation starts from the kelurahan as the spearhead of population registration. In the population service, residents are required to take care of the desired application letter at the village office by following a number of applicable procedures so that in making certain letters it will take quite a long time and energy. For this reason, this letter data collection system was created. In the process of making this Information System using the waterfall method. The system design is explained by using DFD and ERD as a tool to describe the database design. This correspondence service information system is built using the PHP programming language, and the database management system uses Mysql. So it is hoped that with this letter data collection system, it is able to provide better services to the Silaberanti village